Preparation and characterization of poly(2-acrylamido-2-methylpropane-sulfonic acid) grafted chitosan using potassium persulfate as redox initiator - K. Najjar, Abduel Majid; Wan Yunus, Wan Md Zin; Ahmad, Mansor B.; Ab. Rahman, Mohamad Zaki (Wiley, 2000)
A grafted material based on chitosan and 2-acrylamido-2-methylpropanesulfonic acid (AMPS) has been successfully prepared in homogenous solution using potassium persulfate as a redox initiator. The grafted copolymer was precipitated during the reaction polymerization. The effects of the reaction temperature and chitosan–potassium persulfate contact time as well as concentrations of AMPS, potassium persulfate, and acetic acid on grafting yield were investigated. The percentage of grafting is gradually increased with the increasing of the AMPS concentration. The extent of grafting can be controlled by setting the appropriate reaction conditions. The maximum percentage of grafting was about 180% under the optimum conditions (1% v/v acetic acid, 50°C reaction temperature, 10 min chitosan–potassium persulfate mixing period, 0.37 mmol of potassium persulfate, and 28.96 mmol AMPS). The grafted chitosan was insoluble in the acid of the grafting.